Negative electrode active material, negative electrode comprising same, secondary battery comprising same, and method for manufacturing negative electrode active material

By using silicon-based particles of SiOx and Mg compounds in lithium secondary batteries and setting a carbon layer on their surface, controlling the content of N and H elements to form a Mg-Si-O-N film, the filling of silicon-based oxide negative electrode active material is solved. The problems of volume expansion and low efficiency during discharge process improve the discharge capacity and life characteristics of the battery.

CN119301769APending Publication Date: 2025-01-10LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380043188.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-11-09
Filing Date
2023-11-10
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the existing lithium secondary batteries, silicon-based oxide negative electrode active materials expand/contract severely during charging and discharging, resulting in high irreversible capacity and low initial efficiency. The reaction of metal oxides with moisture caused by doping metal increases pH and viscosity. Unstable, reducing charge and discharge efficiency.

Method used

Silicon-based particles containing SiOx (0

Benefits of technology

The hardness and conductivity of the negative electrode active material are improved, the discharge capacity, initial efficiency and life characteristics of the secondary battery are improved, and volume expansion and electrolyte side reactions are suppressed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to a negative electrode active material, a negative electrode comprising the same, a secondary battery comprising the same, and a method for manufacturing the negative electrode active material. The negative electrode active material includes: a first electrode including SiOx (0lt; xlt; 2) silicon-based particles of a Mg compound; and a carbon layer provided on at least a portion of the silicon-based particles, in which the negative electrode active material contains an element N and an element H, in which a total content of the element N and the element H is 250 ppm or more and less than 3000 ppm based on 100 parts by weight of the negative electrode active material, and in which a weight ratio of the element H to the element N is 1 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the priority and benefits of Korean Patent Application No. 10-2022-0150562, filed with the Korean Intellectual Property Office on November 11, 2022, and Korean Patent Application No. 10-2023-0154765, filed with the Korean Intellectual Property Office on November 9, 2023. The entire contents of the Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to a negative electrode active material, a negative electrode including the same, a secondary battery including the negative electrode, and a method of manufacturing the negative electrode active material. Background Art

[0003] Recently, with the rapid popularization of electronic devices using batteries, such as mobile phones, laptop computers, and electric vehicles, the demand for small, lightweight, and relatively high-capacity secondary batteries has increased rapidly. In particular, lithium secondary batteries have become a driving power source for portable devices that attract much attention due to their light weight and high energy density. Therefore, research and development work for improving the performance of lithium secondary batteries are being actively carried out.

[0004] Generally, a lithium secondary battery includes a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, an electrolyte, an organic solvent, and the like. In addition, the positive electrode and the negative electrode can be formed on current collectors each having an active material layer including a positive electrode active material and a negative electrode active material. Generally, for the positive electrode, lithium-containing metal oxides such as LiCoO2 and LiMn2O4 are used as the positive electrode active material, and for the negative electrode, a carbon-based active material or a silicon-based active material不含锂 is used as the negative electrode active material.

[0005] Among negative electrode active materials, silicon-based active materials have attracted much attention because they have a higher capacity and excellent high-speed charging characteristics than carbon-based active materials. However, the disadvantages of silicon-based active materials are that the degree of volume expansion / contraction during charge and discharge is high and the irreversible capacity is high, resulting in low initial efficiency.

[0006] On the other hand, among silicon-based active materials, silicon-based oxides, specifically silicon-based oxides represented by SiO x (0 < x < 2) have the advantage that the degree of volume expansion / contraction during charge and discharge is lower than that of other silicon-based active materials such as silicon (Si). However, the disadvantages of the silicon-based oxides are also that the initial efficiency is reduced due to the presence of an irreversible capacity.

[0007] In this regard, studies have been conducted to reduce the irreversible capacity and improve the initial efficiency by doping or inserting metals such as Li, Al, and Mg into silicon-based oxides. However, the problem with the negative electrode paste containing silicon-based oxides doped with metals as the negative electrode active material is that the metal oxides formed by doping the metals react with moisture, thereby increasing the pH of the negative electrode paste and changing the viscosity. As a result, the state of the manufactured negative electrode is poor, and the charge-discharge efficiency of the negative electrode is reduced.

[0008] In addition, as the cycle progresses, the negative electrode expands, causing a large number of side reactions with the electrolyte.

[0009] Therefore, it is necessary to develop a negative electrode active material that can suppress the surface reaction of the negative electrode active material containing silicon-based oxides, improve the phase stability of the paste, and improve the charge-discharge efficiency of the negative electrode manufactured from the negative electrode active material.

[0010] Prior art documents

[0011] Patent documents

[0012] (Patent Document 1) Korean Patent Application Publication No. 10-2019-0090730 Summary of the Invention

[0013] Technical Problem

[0014] The present invention relates to a negative electrode active material, a negative electrode containing the same, a secondary battery containing the negative electrode, and a method for manufacturing the negative electrode active material.

[0015] Technical Solution

[0016] An exemplary embodiment of the present invention provides a negative electrode active material, which includes: silicon-based particles containing SiO x (0 < x < 2) and a Mg compound; and a carbon layer provided on at least a part of the silicon-based particles, wherein the negative electrode active material contains N element and H element, wherein based on 100 parts by weight of the negative electrode active material, the total content of N element and H element is 250 ppm or more and less than 3000 ppm, and wherein the weight ratio of H element to N element is 1 or less.

[0017] Another exemplary embodiment of the present invention provides a negative electrode.

[0018] Still another exemplary embodiment of the present invention provides a secondary battery containing the negative electrode.

[0019] Another exemplary embodiment of the present invention provides a method for manufacturing a negative electrode active material according to the present invention, the method comprising: gasifying Si powder, SiO2 powder and Mg separately and mixing them, and then cooling the mixed gas to form silicon-based particles; and mixing the silicon-based particles with a carbon-based material to set a carbon layer on at least a portion of the surface of the silicon-based particles.

[0020] Beneficial Effects

[0021] The negative electrode active material according to an exemplary embodiment of the present invention includes a Mg compound, and the sum of N and H in the negative electrode active material is 250 ppm or more and less than 3000 ppm, and the weight ratio of H to N is 1 or less. The negative electrode active material satisfying the above characteristics has increased hardness and elasticity, which is advantageous for expansion of the negative electrode, and the carbon layer has increased conductivity, which has the effect of improving life characteristics.

[0022] Therefore, a negative electrode including the negative electrode active material and a secondary battery including the negative electrode according to an exemplary embodiment of the present invention have an effect of improving discharge capacity, initial efficiency, resistance properties, and / or lifespan characteristics of a battery. DETAILED DESCRIPTION

[0023] The present specification will be described in more detail below.

[0024] In the present specification, unless explicitly described to the contrary, when a part is referred to as “comprising” a certain component, this means that the part may further include another component, without excluding the other component.

[0025] Throughout this specification, when a component is referred to as being 'on' another component, the component may be in direct contact with the other component, or an intervening component may also be present.

[0026] It should be understood that the terms or words used throughout this specification should not be interpreted as limited to their ordinary meanings or dictionary meanings, but should be interpreted as having meanings and concepts consistent with the technical ideas of the present invention based on the concepts that the inventor can appropriately define the words or terms in order to explain the principles of the present invention in the best manner.

[0027] The terms used in this specification are only used to describe illustrative exemplary embodiments of the present invention, but are not intended to limit the present invention. As used herein, the singular forms "a", "an" and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.

[0028] In this specification, the crystallinity of the structure contained in the negative electrode active material can be confirmed by X-ray diffraction analysis, and the X-ray diffraction analysis can be performed by using an X-ray diffractometer (XRD) (product name: D4-endavor, manufacturer: Bruker Corporation), or by appropriately using a device used in the art other than the above device.

[0029] In this specification, the presence or absence and the content of elements in the negative electrode active material can be confirmed by ICP analysis, and the ICP analysis can be performed by using an inductively coupled plasma atomic emission spectrometer (ICPAES, Perkin-Elmer 7300).

[0030] In this specification, the average particle diameter (D 50 ) can be defined as the particle diameter corresponding to 50% cumulative volume in the particle size distribution curve (the curve of the particle size distribution diagram) of the particles. The average particle diameter (D 50 ) can be measured by, for example, the laser diffraction method. In the laser diffraction method, the particle diameter in the range from the sub-micron region to several millimeters can generally be measured, and highly reproducible and high-resolution results can be obtained.

[0031] Preferred embodiments of the present invention will be described in detail below. However, it should be understood that the embodiments of the present invention can be modified into various forms, and the scope of the present invention is not limited to the embodiments described below.

[0032] <Negative electrode active material>

[0033] An exemplary embodiment of the present invention provides a negative electrode active material, which includes: silicon-based particles containing SiO x (0 < x < 2) and a Mg compound; and a carbon layer provided on at least a part of the silicon-based particles, wherein the negative electrode active material contains N element and H element, wherein based on 100 parts by weight of the negative electrode active material, the total content of N element and H element is 250 ppm or more and less than 3000 ppm, and wherein the weight ratio of H element to N element is 1 or less.

[0034] The negative electrode active material according to an exemplary embodiment of the present invention includes silicon-based particles. The silicon-based particles contain SiO x (0 < x < 2) and a Mg compound.

[0035] The SiO x (0 < x < 2) can correspond to the matrix in the silicon-based particles. The SiO x (0 < x < 2) can be in a form containing Si and / or SiO2, and Si can form a phase. For example, the SiO x(0 < x < 2) can be a composite containing amorphous SiO2 and Si crystals. That is, x corresponds to the number ratio of O to Si contained in the SiO x (0 < x < 2). When the silicon-based particles contain the SiO x (0 < x < 2), the discharge capacity of the secondary battery can be improved.

[0036] The Mg compound can correspond to a dopant in the silicon-based particles. The Mg compound can exist in the silicon-based particles in at least one form of magnesium atoms, magnesium silicate, magnesium silicide, and magnesium oxide. When the silicon-based particles contain the Mg compound, the initial efficiency is improved.

[0037] The Mg compound can be distributed on the surface and / or inside of the silicon-based particles in a form doped into the silicon-based particles. The Mg compound can be distributed on the surface and / or inside of the silicon-based particles to control the volume expansion / contraction of the silicon-based particles to an appropriate level and prevent damage to the active material. In addition, in terms of reducing the ratio of the irreversible phase (e.g., SiO2) of the silicon-based oxide particles to improve the efficiency of the active material, the Mg compound can be contained.

[0038] The Mg compound can contain at least one selected from the group consisting of magnesium silicate, magnesium silicide, and magnesium oxide. The magnesium silicate can contain at least one of Mg2SiO4 and MgSiO3. The magnesium silicide can contain Mg2Si. The magnesium oxide can contain MgO.

[0039] The Mg compound can exist in the form of magnesium silicate. The magnesium silicate can be classified into crystalline magnesium silicate and amorphous magnesium silicate.

[0040] The Mg compound can exist in the silicon-based particles in the form of at least one type of magnesium silicate of Mg2SiO4 and MgSiO3.

[0041] Based on a total of 100 parts by weight of the negative electrode active material, the content of Mg element can be 0.1 part by weight to 40 parts by weight, specifically 0.1 part by weight to 20 parts by weight or 0.1 part by weight to 10 parts by weight, and more specifically 0.5 part by weight to 8 parts by weight. If the content of Mg exceeds the above range, the initial efficiency increases with the increase of the content of Mg, but the discharge capacity decreases. Therefore, when the above range is satisfied, an appropriate discharge capacity and initial efficiency can be achieved.

[0042] The content of Mg element can be confirmed by ICP analysis. Specifically, a predetermined amount (about 0.01 g) of negative electrode active material is accurately weighed, transferred to a platinum crucible, and completely decomposed on a hot plate by adding nitric acid, hydrochloric acid and sulfuric acid thereto. Then, by using an inductively coupled plasma atomic emission spectrometer (ICP-AES, Perkin-Elmer 7300), at the inherent wavelength of the element to be analyzed, a reference calibration curve is obtained by measuring the intensity of a standard liquid prepared using a standard solution (5 mg / kg). Subsequently, the pretreated sample solution and a blank sample are introduced into a spectrometer, the actual intensity is calculated by measuring the intensity of each, the concentration of each component is calculated based on the obtained calibration curve, and the conversion is performed so that the sum of the calculated concentrations of the components is equal to the theoretical value, and the element content of the prepared negative electrode active material can be analyzed.

[0043] In an exemplary embodiment of the present invention, the silicon-based particles may contain additional metal atoms. The metal atoms may be present in the silicon-based particles in the form of at least one of metal atoms, metal silicates, metal silicides, and metal oxides. The metal atoms may contain at least one selected from the group consisting of Mg, Li, Al, and Ca. Thus, the initial efficiency of the negative electrode active material can be improved.

[0044] In an exemplary embodiment of the present invention, the silicon-based particles are provided with a carbon layer on at least a portion of their surface. In this case, the carbon layer may be coated on at least a portion of the surface, that is, may be partially coated on the particle surface, or may be coated on the entire surface of the particle. The carbon layer imparts conductivity to the negative electrode active material, thereby improving the initial efficiency, life characteristics, and battery capacity characteristics of the secondary battery.

[0045] In an exemplary embodiment of the present invention, the carbon layer includes amorphous carbon. In addition, the carbon layer may further include crystalline carbon.

[0046] The crystalline carbon may further improve the conductivity of the negative electrode active material. The crystalline carbon may include at least one selected from the group consisting of fullerene, carbon nanotube, and graphene.

[0047] The amorphous carbon can appropriately maintain the strength of the carbon layer to suppress the expansion of the silicon-based particles. The amorphous carbon can be a carbide of at least one substance selected from the group consisting of tar, pitch, and other organic materials, or can be a carbon-based material formed by using hydrocarbons as a source for chemical vapor deposition.

[0048] The carbide of the other organic material may be a carbide of an organic substance selected from sucrose, glucose, galactose, fructose, lactose, mannose, ribose, aldohexose or ketohexose, and a combination thereof.

[0049] The hydrocarbon may be a substituted or unsubstituted aliphatic or alicyclic hydrocarbon or a substituted or unsubstituted aromatic hydrocarbon. The aliphatic or alicyclic hydrocarbon of the substituted or unsubstituted aliphatic or alicyclic hydrocarbon may be methane, ethane, ethylene, acetylene, propane, butane, butene, pentane, isobutane, hexane, etc. The aromatic hydrocarbon of the substituted or unsubstituted aromatic hydrocarbon may be benzene, toluene, xylene, styrene, ethylbenzene, diphenylmethane, naphthalene, phenol, cresol, nitrobenzene, chlorobenzene, indene, coumarone, pyridine, anthracene, phenanthrene, etc.

[0050] In an exemplary embodiment of the present invention, the carbon layer may be an amorphous carbon layer.

[0051] In an exemplary embodiment of the present invention, the content of the carbon layer may be 0.1 to 50 parts by weight, 0.1 to 30 parts by weight, or 0.1 to 20 parts by weight, based on a total of 100 parts by weight of the negative electrode active material. More specifically, the content of the carbon layer may be 0.5 to 15 parts by weight, 1 to 10 parts by weight, or 1 to 5 parts by weight. When the above range is met, the capacity and efficiency of the negative electrode active material can be prevented from being reduced.

[0052] In an exemplary embodiment of the present invention, the thickness of the carbon layer may be 1 nm to 500 nm, specifically 5 nm to 300 nm. When the above range is met, the conductivity of the negative electrode active material is improved, the volume change of the negative electrode active material is easily suppressed, and the side reaction between the electrolyte and the negative electrode active material is suppressed, thereby improving the initial efficiency and / or life of the battery.

[0053] Specifically, the carbon layer may be formed by chemical vapor deposition (CVD) using at least one hydrocarbon gas selected from the group consisting of methane, ethane, and acetylene.

[0054] In the present invention, the crystallinity of the carbon layer can be confirmed by calculating the D / G band ratio according to Raman spectroscopy. Specifically, the measurement can be performed as follows: using a Renishaw 2000 Raman microscope system and 532 nm laser excitation, using a 100x optical lens, using a low laser power density, and an exposure time of 30 seconds to avoid laser thermal effects. In order to reduce the deviation according to the position, a total of 25 points can be measured for an area of ​​5 μm×5 μm, and a Lorentz function fitting can be used. Thereafter, the average values ​​of the D band and the G band can be calculated.

[0055] In an exemplary embodiment of the present invention, the negative electrode active material may further include N element and H element.

[0056] In an exemplary embodiment of the present invention, the total content of N and H elements may be 250 ppm or more and less than 3000 ppm. Specifically, the total content may be 280 ppm or more and 2000 ppm or less, 280 ppm or more and 1800 ppm or less, or 300 ppm or more and 1800 ppm or less. The lower limit of the content of N and H elements may be 250 ppm, 280 ppm, 290 ppm, 300 ppm, 350 ppm, 400 ppm, 450 ppm, 500 ppm, 550 ppm, 600 ppm or 700 ppm, and the upper limit of the content of N and H elements may be 2900 ppm, 2500 ppm, 2000 ppm, 1800 ppm, 1600 ppm, 1500 ppm, 1300 ppm or 1000 ppm.

[0057] When the contents of N and H elements meet the above ranges, the Mg-Si-ON film is effectively formed on the surface of the silicon-based particles, so that the expansion of the material can be controlled and the conductivity of the carbon layer is increased, which has the effect of improving the life characteristics. On the other hand, if the contents of N and H are lower than the above ranges, the Mg-Si-ON film is not well formed on the surface of the silicon-based particles, making it difficult to control the expansion, and if the contents of N and H exceed the above ranges, there is a problem that the expansion is difficult to control because the hardness and elasticity of the Mg-Si-ON film deteriorate. Specifically, in the case of a Mg-Si-ON structure rather than a structure such as Si-ON glass, Mg can be combined with O to provide a fairly strong structure. In the present invention, the contents of N and H meet the above specific ranges and specific ratios, which is beneficial to the formation of the Mg-Si-ON structure, so that the hardness and elasticity can be improved, thereby controlling the expansion. If the contents of N and H are too high or do not meet the above ratios, the possibility of forming Si-OH or other structures is relatively higher than the possibility of forming Mg-Si-ON.

[0058] The content and ratio of the above-mentioned N and H elements can be determined by the process conditions or materials used in the process of manufacturing the negative electrode active material. For example, the above range can be met by mixing an appropriate amount of a material containing an appropriate amount of N and H, such as ammonia, with a material providing a carbon source when forming the carbon layer.

[0059] In an exemplary embodiment of the present invention, the negative electrode active material may include a Mg-Si-ON film disposed on the surface of the silicon-based particles. The Mg-Si-ON film may be in the form of silicon oxynitride having Si-N bonds.

[0060] N may exist in the form of silicon oxynitride on the surface of the silicon-based particles containing the Mg compound, or may exist in the form of being contained in the carbon layer. Specifically, N may have a Si-N bond and exist in the form of silicon oxynitride on the surface of the silicon-based particles, or N may be contained in the carbon layer in the form of having a CN bond.

[0061] That is, at least a portion of N in the negative active material according to the present invention may exist as a Si—N bond. In another exemplary embodiment, at least a portion of N in the negative active material according to the present invention may be included in the carbon layer.

[0062] H may exist on the surface of the silicon-based particle including the Mg compound in the form of having a Si-OH bond, or may exist in the form of being contained in the carbon layer. Specifically, H may be contained in the carbon layer in the form of having a CH bond.

[0063] In an exemplary embodiment of the present invention, the content of N may be 125 ppm or more and less than 3000 ppm. Specifically, the content may be 150 ppm or more and 2500 ppm or less, 175 ppm or more and 2000 ppm or less, 200 ppm or more and 1500 ppm or less, or 210 ppm or more and 1200 ppm or less. The lower limit of the content of N may be 125 ppm, 150 ppm, 175 ppm, 200 ppm, 210 ppm, 220 ppm, 250 ppm, 350 ppm, 400 ppm, or 430 ppm, and the upper limit of the content of N may be 2900 ppm, 2500 ppm, 2000 ppm, 1500 ppm, 1200 ppm, 1000 ppm, 800 ppm, 600 ppm, or 500 ppm.

[0064] When the N content satisfies the above range, the Mg-Si-ON film is effectively formed on the surface of the silicon-based particles, which has the effect of controlling the expansion of the material to improve the life characteristics, increasing the conductivity of the carbon layer, and thus improving the life characteristics. On the other hand, if the N content is lower than the above range, the Mg-Si-ON film is not formed on the surface of the silicon-based particles, making it difficult to control the expansion, and if the N content exceeds the above range, there is a problem that it is difficult to control the expansion because the hardness and elasticity of the Mg-Si-ON film deteriorate.

[0065] In an exemplary embodiment of the present invention, the content of H may be 1 ppm or more and less than 1500 ppm. Specifically, the content may be 10 ppm or more and 1200 ppm or less, 50 ppm or more and 1000 ppm or less, 70 ppm or more and 800 ppm or less, or 70 ppm or more and 600 ppm or less. The lower limit of the content of H may be 1 ppm, 10 ppm, 50 ppm, 70 ppm, 80 ppm, 100 ppm, 200 ppm or 300 ppm, and the upper limit of the content of H may be 1400 ppm, 1200 ppm, 1000 ppm, 800 ppm, 600 ppm, 500 ppm or 400 ppm.

[0066] When the H content satisfies the above range, the functional groups in the carbon layer are less, so the side reaction with the electrolyte is reduced and the life is improved accordingly. On the other hand, if the H content is lower than the above range, the hydrophobicity of the active material becomes too large, and there is a problem of poor dispersibility in the aqueous slurry. If the H content exceeds the above range, there is a problem that the functional groups are excessively present in the carbon layer, resulting in an increase in the side reaction with the electrolyte, thereby deteriorating the battery performance.

[0067] In an exemplary embodiment of the present invention, the weight ratio of H to N may be 1 or less. Specifically, the weight ratio may be greater than 0 and 1 or less or 0.1 or more and 1 or less.

[0068] The weight ratio of H to N may be less than 0.95, less than 0.9, less than 0.85, or less than 0.8, and may be greater than 0, greater than 0, greater than 0.01, greater than 0.1, greater than 0.1, greater than 0.2, or greater than 0.3. When the weight ratio of H to N satisfies the above range, the negative electrode active material is well dispersed in the aqueous slurry, and the conductivity of the negative electrode active material and the withdrawal of Li ions are excellent. On the other hand, if the weight ratio of H to N is lower than the above range, many defects appear in the carbon layer to increase the side reaction with the electrolyte, resulting in poor cycle performance, and if the weight ratio exceeds the above range, the hydrophobicity of the carbon layer increases, resulting in poor dispersibility in the aqueous slurry.

[0069] In this specification, the content (concentration) of N and H elements can be measured by putting 0.1 g of the negative electrode active material sample into a crucible and putting the crucible into an ONH analyzer (Bruker Corporation, G8 Galileo).

[0070] The average particle size of the negative electrode active material (D 50) can be 0.1 μm to 30 μm, specifically 1 μm to 20 μm, and more specifically 1 μm to 10 μm. When the above range is met, the structural stability of the active material during charge and discharge is ensured, and the problem that the level of volume expansion / contraction increases as the particle size becomes too large can be prevented, and the problem that the initial efficiency decreases when the particle size is too small can also be prevented.

[0071] The BET specific surface area of ​​the negative electrode active material can be 1 m 2 / g to 100 m 2 / g, specifically 1 m 2 / g to 70m 2 / g, more specifically 1 m 2 / g to 50 m 2 / g, for example, 2 m 2 / g to 30 m 2 When the above range is satisfied, a side reaction between the electrolyte and the negative electrode active material can be reduced during charge and discharge of the battery, and thus the life characteristics of the battery can be improved.

[0072] <Method for producing negative electrode active material>

[0073] An exemplary embodiment of the present invention provides a method for manufacturing a negative electrode active material, the method comprising: gasifying Si powder, SiO2 powder and Mg separately and mixing them, and then cooling the mixed gas to form silicon-based particles; and mixing the silicon-based particles with a carbon-based material to set a carbon layer on at least a portion of the surface of the silicon-based particles.

[0074] The Si powder and the SiO2 powder can be manufactured by heating the powder in a vacuum to gasify it and then depositing the gasified mixed gas. In this case, the Si powder and the SiO2 powder can be gasified by heating them individually, or can be gasified by heating the powder in a mixed state.

[0075] The Si powder and the SiO 2 powder may be included in a weight ratio of 2:8 to 8:2, and specifically, may be included in a weight ratio of 4:6 to 6:4 or 5:5.

[0076] Specifically, the Si powder and the SiO 2 powder may be heat-treated at 1300° C. to 1800° C., 1400° C. to 1800° C., or 1400° C. to 1600° C. under vacuum.

[0077] The mixed gas vaporized by the heat treatment can be cooled under vacuum and deposited as a solid phase. In addition, the preliminary silicon-based particles can be produced by heat treating the deposited solid phase in an inert atmosphere. The heat treatment can be performed at 500°C to 1000°C or 700°C to 900°C.

[0078] A carbon layer may be provided on the surface of the silicon-based particles.

[0079] The carbon layer can be formed, for example, by using chemical vapor deposition (CVD) in which a carbon-based material such as a hydrocarbon gas is used, or by carbonizing a material serving as a carbon source.

[0080] Specifically, the carbon layer may be formed by placing the formed silicon-based particles into a reactor and then depositing a hydrocarbon gas by chemical vapor deposition (CVD) at 600° C. to 1200° C. The hydrocarbon gas may be at least one hydrocarbon gas selected from the group consisting of methane, ethane, propane, and acetylene, and may be heat-treated at 900° C. to 1000° C.

[0081] In this case, N and H within the above ranges may be included in the negative electrode active material by the following method.

[0082] (1) A method of performing a step of heat treating the silicon-based particles in a nitrogen atmosphere after forming the silicon-based particles.

[0083] In an exemplary embodiment of the present invention, Si powder, SiO2 powder and Mg may be gasified separately and then mixed, the mixed gas may be cooled to form silicon-based particles, and then the silicon-based particles may be heat-treated in a nitrogen (N2) atmosphere. Specifically, the silicon-based particles containing the Mg compound may be heat-treated in a nitrogen atmosphere to introduce silicon oxynitride into the surface of the silicon-based particles.

[0084] In this case, the heat treatment temperature may be 850°C to 1200°C, specifically 900°C to 1100°C.

[0085] Thereafter, a carbon layer may be formed on the surface of the silicon-based particles by using the above-mentioned chemical vapor deposition (CVD) method under an Ar atmosphere.

[0086] (2) A method of performing the step of mixing the silicon-based particles with the carbon-based material under a N2 atmosphere to provide a carbon layer on at least a portion of the surface of the silicon-based particles.

[0087] In an exemplary embodiment of the present invention, the step of mixing the silicon-based particles with the carbon-based material to provide a carbon layer on at least a portion of the surface of the silicon-based particles may be performed under a N 2 atmosphere.

[0088] In this case, the carbon layer may be formed on the surface of the silicon-based particle by using a chemical vapor deposition (CVD) method in the above step. In this case, the carbon-based material may be a hydrocarbon gas.

[0089] In another exemplary embodiment, in the above step, the carbon layer may be formed by coating a carbon source on the surface of the silicon-based particles. In this case, the carbon-based material may be pitch.

[0090] In an exemplary embodiment of the present invention, before the step of mixing the silicon-based particles with the carbon-based material to provide a carbon layer on at least a portion of the surface of the silicon-based particles, a step of heat treating the silicon-based particles under a N2 atmosphere may be further performed.

[0091] In this case, the heat treatment temperature may be 850°C to 1200°C, specifically 900°C to 1100°C.

[0092] (3) In the step of mixing the silicon-based particles with a carbon-based material to provide a carbon layer on at least a portion of the surface of the silicon-based particles, a method of further including NH3 gas in addition to the carbon-based material.

[0093] In an exemplary embodiment of the present invention, in the step of providing a carbon layer on at least a portion of the surface of the silicon-based particle, NH 3 may be further added in addition to the carbon-based material.

[0094] In this case, the weight ratio of the carbon-based material to NH3 may be 0.8: 1 to 30: 1. Specifically, the weight ratio may be 0.8: 1 to 20: 1, 0.8: 1 to 10: 1, 0.8: 1 to 5: 1, 0.8: 1 to 2: 1, 0.8: 1 to 1.5: 1, or 0.8: 1 to 1.2: 1. When the above range is met, N and H are introduced into the negative electrode active material in an appropriate range, thereby providing the negative electrode active material with appropriate hardness and elasticity and improving conductivity.

[0095] The steps may be performed using a chemical vapor deposition (CVD) method.

[0096] The negative electrode active material according to the present invention can be produced by appropriately using the above methods (1) to (3), but the present invention is not limited thereto. For example, the negative electrode active material according to the present invention can be produced by appropriately using a combination of the above methods (1) to (3).

[0097] When a negative electrode active material is formed using the above method, N and H are introduced into the negative electrode active material in an appropriate range, thereby being able to improve the performance of a battery using the same.

[0098] <Negative electrode>

[0099] A negative electrode according to an exemplary embodiment of the present invention may include the above-mentioned negative electrode active material.

[0100] Specifically, the negative electrode may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer may include the negative electrode active material. In addition, the negative electrode active material layer may further include a binder, a thickener and / or a conductive material.

[0101] The negative electrode active material layer may be formed by applying a negative electrode slurry including a negative electrode active material, a binder, a thickener and / or a conductive material to at least one surface of a current collector, and drying and rolling it.

[0102] The negative electrode slurry may further include additional negative electrode active materials.

[0103] As the additional negative electrode active material, a compound capable of reversibly intercalating and deintercalating lithium can be used. Specific examples include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal substances capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy; metal oxides capable of doping and dedoping lithium, such as SiO β (0<β<2), SnO2, vanadium oxide, lithium titanium oxide, and lithium vanadium oxide; or a composite containing a metal substance and a carbonaceous material, such as a Si-C composite or a Sn-C composite, and any one thereof or a mixture of two or more thereof can be used. In addition, a metallic lithium film can be used as a negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Representative examples of low-crystalline carbon include soft carbon and hard carbon, and representative examples of high-crystalline carbon include amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, floating graphite, pyrolytic carbon, mesophase pitch-based carbon fibers, mesophase carbon microbeads, mesophase pitch and high-temperature fired carbon such as coke derived from petroleum or coal tar pitch.

[0104] The additional negative electrode active material may be a carbon-based negative electrode active material.

[0105] In an exemplary embodiment of the present invention, a weight ratio of the negative electrode active material to the additional negative electrode active material included in the negative electrode slurry may be 10:90 to 90:10, specifically 10:90 to 50:50.

[0106] The negative electrode slurry may include a solvent for forming the negative electrode slurry. Specifically, in terms of promoting dispersion of components, the solvent for forming the negative electrode slurry may include at least one selected from the group consisting of distilled water, ethanol, methanol, and isopropanol, specifically distilled water.

[0107] The negative electrode slurry containing the negative electrode active material according to an exemplary embodiment of the present invention may have a pH of 7 to 11 at 25° C. When the pH of the negative electrode slurry satisfies the above range, the rheology of the slurry is stabilized. On the other hand, when the pH of the negative electrode slurry is less than 7 or the pH of the negative electrode slurry exceeds 11, carboxymethyl cellulose (CMC) used as a thickener decomposes, resulting in a decrease in the viscosity of the slurry and a decrease in the dispersion of the active material contained in the slurry.

[0108] There is no particular limitation on the negative electrode current collector as long as it has conductivity without causing chemical changes in the battery. For example, for the current collector, copper, stainless steel, aluminum, nickel, titanium, fired carbon, aluminum or stainless steel each surface-treated with carbon, nickel, titanium, silver, etc., etc. can be used. Specifically, for the current collector, transition metals such as copper and nickel that adsorb carbon well can be used. The thickness of the current collector can be 6 μm to 20 μm. However, the thickness of the current collector is not limited thereto.

[0109] The adhesive may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid, and the above materials in which hydrogen is replaced by Li, Na, Ca, etc., and may also include various copolymers thereof.

[0110] There is no particular limitation on the conductive material as long as it has conductivity and does not cause chemical changes in the battery. For example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers such as carbon fibers and metal fibers; conductive tubes such as carbon nanotubes; fluorocarbons; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc.

[0111] The thickener may be carboxymethyl cellulose (CMC), but is not limited thereto, and any thickener used in the art may be appropriately used.

[0112] In an exemplary embodiment of the present invention, a weight ratio of the negative electrode active material to the additional negative electrode active material included in the negative electrode slurry may be 1:99 to 30:70, specifically 5:95 to 30:70 or 10:90 to 20:80.

[0113] In an exemplary embodiment of the present invention, the content of all negative electrode active materials contained in the negative electrode slurry may be 60 to 99 parts by weight, specifically 70 to 98 parts by weight, based on 100 parts by weight of the solid content of the negative electrode slurry in total.

[0114] In an exemplary embodiment of the present invention, the binder may be included in an amount of 0.5 to 30 parts by weight, for example 1 to 20 parts by weight, based on 100 parts by weight of the solid content of the negative electrode slurry in total.

[0115] In an exemplary embodiment of the present invention, the conductive material may be contained in an amount of 0.5 to 25 parts by weight, specifically 1 to 20 parts by weight, based on 100 parts by weight of the solid content of the negative electrode slurry in total.

[0116] In an exemplary embodiment of the present invention, the thickener may be included in an amount of 0.5 to 25 parts by weight, specifically 0.5 to 20 parts by weight, and more specifically 1 to 20 parts by weight, based on 100 parts by weight of the solid content of the negative electrode slurry.

[0117] The negative electrode slurry according to an exemplary embodiment of the present invention may further include a solvent for forming the negative electrode slurry. Specifically, in terms of promoting dispersion of components, the negative electrode slurry forming solvent may include at least one selected from the group consisting of distilled water, ethanol, methanol and isopropanol, specifically distilled water.

[0118] In an exemplary embodiment of the present invention, the solid content of the negative electrode slurry may be 20 parts by weight to 75 parts by weight, specifically 30 parts by weight to 70 parts by weight, based on 100 parts by weight in total of the negative electrode slurry.

[0119] <Secondary Battery>

[0120] A secondary battery according to an exemplary embodiment of the present invention may include the negative electrode according to an exemplary embodiment of the present invention described above. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the negative electrode described above. Since the negative electrode has been described above, its detailed description is omitted.

[0121] The positive electrode may include a positive electrode current collector, and a positive electrode active material layer formed on the positive electrode current collector and including a positive electrode active material.

[0122] In the positive electrode, there is no particular restriction on the positive electrode collector, as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, fired carbon, aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., etc. can be used. In addition, the thickness of the positive electrode collector can generally be 3 μm to 500 μm, and the surface of the collector can be formed with microscopic concave-convex to enhance the adhesion of the positive electrode active material. For example, the positive electrode collector can be used in various shapes, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0123] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2) or a compound substituted by one or more transition metals; lithium iron oxide such as LiFe3O4; lithium manganese oxide such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides, such as LiV3O8, V2O5 and Cu2V2O7; Ni-site lithium nickel oxide, composed of the chemical formula LiNi 1-c2 M c2 O2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≤c2≤0.5); lithium manganese composite oxide, represented by the chemical formula LiMn 2-c3 M c3 O2 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and satisfies 0.01≤c3≤0.1) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu and Zn); LiMn2O4, wherein a portion of Li in the chemical formula is replaced by an alkaline earth metal ion, etc., but is not limited thereto. The positive electrode may be Li metal.

[0124] The positive electrode active material layer may further include a positive electrode conductive material and a positive electrode binder in addition to the positive electrode active material described above.

[0125] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without particular limitation, as long as the positive electrode conductive material has electronic conductivity without causing chemical changes in the constituted battery. Specific examples may include graphite, such as natural graphite and artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and the like, and any one thereof or a mixture of two or more thereof may be used.

[0126] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers, etc., and any one thereof or a mixture of two or more thereof may be used.

[0127] The diaphragm is used to separate the negative electrode and the positive electrode and provide a path for lithium ion movement, wherein any diaphragm can be used as the diaphragm without particular limitation, as long as it is commonly used in secondary batteries, in particular, it may be preferred to use a diaphragm having high moisture retention capacity for the electrolyte and low resistance to the movement of electrolyte ions. Specifically, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer and an ethylene / methacrylate copolymer, or a laminated structure of more than two layers thereof. In addition, ordinary porous nonwoven fabrics can be used, for example, nonwoven fabrics formed by high melting point glass fibers, polyethylene terephthalate fibers, etc. In addition, a coated diaphragm comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a diaphragm with a monolayer or multilayer structure can be selectively used.

[0128] Examples of the electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten inorganic electrolyte, which may be used to manufacture a lithium secondary battery, but are not limited thereto.

[0129] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.

[0130] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate or ethyl propionate can be used.

[0131] Especially, in carbonate system organic solvent, ethylene carbonate and propylene carbonate as cyclic carbonate are high viscosity organic solvents and they have high dielectric constant, thereby can dissociate lithium salt well, therefore can preferably use.When cyclic carbonate and linear carbonate with low viscosity and low dielectric constant such as dimethyl carbonate or diethyl carbonate are mixed with use in suitable ratio, can prepare electrolyte with high conductivity, therefore may more preferably use.

[0132] A lithium salt may be used as the metal salt, and the lithium salt is a material that is easily dissolved in a non-aqueous electrolyte, wherein, for example, one or more selected from the group consisting of the following may be used as an anion of the lithium salt: F - , Cl - ,I - 、NO3 - 、N(CN) 2- 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN -and (CF3CF2SO2)2N - .

[0133] In order to improve the life characteristics of the battery, inhibit the decline of the battery capacity, improve the discharge capacity of the battery, etc., in addition to the above-mentioned electrolyte components, the electrolyte may also contain one or more additives, such as halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme dimethyl ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.

[0134] Another exemplary embodiment of the present invention provides a battery module including a secondary battery as a unit cell and a battery pack including the battery module. Since the battery module and the battery pack include secondary batteries having high capacity, high rate capability, and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the group consisting of: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0135] Invention Mode

[0136] Preferred embodiments will be provided below to better understand the present invention. However, it will be apparent to those skilled in the art that the embodiments are provided only to illustrate the present invention, and various modifications and changes may be made within the scope and technical spirit of the present invention. Such modifications and changes naturally fall within the scope of the claims contained herein.

[0137] <Examples and Comparative Examples>

[0138] Example 1

[0139] 92 g of Si powder and SiO2 powder mixed in a molar ratio of 1:1 were mixed with 8 g of Mg and heated in a reactor in vacuum to a sublimation temperature of 1,400°C. Then, the mixed gas of sublimated Mg, Si and SiO2 was reacted in a cooling zone under a vacuum state at a cooling temperature of 800°C and condensed into a solid phase to form silicon-based particles. Thereafter, heat treatment was performed in an inert atmosphere at a temperature of 800°C. Then, the silicon-based particles were crushed to a size of 6 μm (D) using a ball mill after adding 15 stainless steel ball media for 3 hours. 50 Then, while Ar gas was flowed to maintain an inert atmosphere, the silicon-based particles were positioned in a hot zone of a CVD device, and methane and ammonia in a weight ratio of 9:1 were introduced into the hot zone at 950° C. using Ar as a carrier gas, and the mixture was heated to 100° C. at 100° C.-1 The reaction was carried out under support for 20 minutes, thereby forming a carbon layer on the surface of the silicon-based particles.

[0140] The material prepared as described above was used as the negative electrode active material of Example 1. 50 The specific surface area is 6 m 2 / g.

[0141] As a result of measurement using an ONH component analyzer, the content of nitrogen contained in the negative electrode active material was 450 ppm, and the content of hydrogen was 360 ppm.

[0142] Example 2

[0143] A negative electrode active material was prepared in the same manner as in Example 1, except that the weight ratio of methane to ammonia was 1:1.

[0144] As a result of measurement using an ONH component analyzer, the content of nitrogen contained in the negative electrode active material was 1100 ppm, and the content of hydrogen was 500 ppm.

[0145] Example 3

[0146] A negative active material was prepared in the same manner as in Example 1, except that the weight ratio of methane to ammonia was 95:5.

[0147] As a result of measurement using an ONH component analyzer, the content of nitrogen contained in the negative electrode active material was 220 ppm, and the content of hydrogen was 80 ppm.

[0148] Comparative Example 1

[0149] A negative active material was prepared in the same manner as in Example 1, except that the weight ratio of methane to ammonia was 1:2.

[0150] As a result of measurement using an ONH component analyzer, the content of nitrogen contained in the negative electrode active material was 1600 ppm, and the content of hydrogen was 1500 ppm.

[0151] Comparative Example 2

[0152] An active material was prepared in the same manner as in Example 1, except that the CVD temperature was 900°C.

[0153] As a result of measurement using an ONH component analyzer, the content of nitrogen contained in the negative electrode active material was 400 ppm, and the content of hydrogen was 430 ppm.

[0154] Comparative Example 3

[0155] An active material was prepared in the same manner as in Example 1, except that the weight ratio of methane to ammonia was 1:3.

[0156] As a result of measurement using an ONH component analyzer, the content of nitrogen contained in the negative electrode active material was 1500 ppm, and the content of hydrogen was 1600 ppm.

[0157] Comparative Example 4

[0158] An active material was prepared in the same manner as in Example 1 except that ammonia was not added.

[0159] As a result of measurement using an ONH component analyzer, the content of nitrogen contained in the negative electrode active material was 10 ppm, and the content of hydrogen was 1 ppm.

[0160] The compositions of the negative electrode active materials prepared in Examples and Comparative Examples are shown in Table 1 below.

[0161]

[0162] In this specification, the content (concentration) of N and H elements is measured by placing 0.1 g of the negative electrode active material sample in a crucible and placing the crucible in an ONH analyzer (Bruker, G8 Galileo). The content of Mg element is confirmed by ICP analysis using an inductively coupled plasma atomic emission spectrometer (ICP-OES of Perkin-Elmer 7300, AVIO 500).

[0163] The content of the carbon layer was confirmed by elemental analysis using combustion (G4 ICARUS from Bruker) under oxygen conditions.

[0164] The negative electrode active material D 50 The analysis was performed by PSD measurement method using Microtrac equipment.

[0165] The specific surface area of ​​the negative electrode active material was measured by degassing at 200° C. for 8 hours and performing N 2 adsorption / desorption at 77 K using a BET measurement apparatus (BEL-SORP-MAX, Bell Co., Japan).

[0166] <Experimental Example: Evaluation of Discharge Capacity, Initial Efficiency and Life (Capacity Retention Rate) Characteristics>

[0167] Negative electrodes and batteries were manufactured using the negative electrode active materials of the examples and comparative examples, respectively.

[0168] A mixture was prepared by mixing the negative electrode active material, carbon black as a conductive material, and polyacrylic acid (PAA) as a binder in a weight ratio of 80:10:10. Thereafter, 7.8 g of distilled water was added to 5 g of the mixture, which was then stirred to prepare a negative electrode slurry. The negative electrode slurry was applied to a copper (Cu) metal film having a thickness of 20 μm as a negative electrode collector, and dried. In this case, the temperature of the circulating air was 60°C. Then, the film was rolled and dried in a vacuum oven at 130°C for 12 hours to prepare a negative electrode.

[0169] By cutting the lithium metal foil into 1.7671 cm 2 A lithium (Li) metal thin film obtained by forming a circular shape of a positive electrode was used as a positive electrode. A porous polyethylene separator was interposed between the positive electrode and the negative electrode, and an electrolyte was injected to manufacture a lithium coin half-cell, wherein 0.5 parts by weight of vinylene carbonate was dissolved in a mixed solution in which ethyl methyl carbonate (EMC) and ethylene carbonate (EC) were mixed in a volume ratio of 7:3, and LiPF6 was dissolved to a concentration of 1M.

[0170] The prepared batteries were charged and discharged to evaluate the discharge capacity, initial efficiency, and capacity retention rate, which are shown in Table 2 below.

[0171] The charge and discharge were performed at 0.1 C for the first and second cycles, and at 0.5 C from the third to 49th cycles. At the 50th cycle, the charge and discharge were terminated in the charged state (lithium was contained in the negative electrode).

[0172] Charging conditions: CC (constant current) / CV (constant voltage) (5mV / 0.005C current cutoff)

[0173] Discharge condition: CC (constant current) condition 1.5V

[0174] The discharge capacity (mAh / g) and initial efficiency (%) were derived from the results after one charge and discharge. Specifically, the initial efficiency (%) was derived by the following calculation.

[0175] Initial efficiency (%) = (first discharge capacity / first charge capacity) × 100

[0176] The capacity retention rate is derived by the following calculation.

[0177] Capacity retention rate (%) = (49th discharge capacity / first discharge capacity) × 100

[0178]

[0179] In Table 2, it can be confirmed that in Examples 1 to 3 using the negative electrode active material according to the present invention, the negative electrode active material contains N and H elements, the total content of N and H elements is 250 ppm or more and less than 3000 ppm based on 100 parts by weight of the negative electrode active material, the weight ratio of H element to N is less than 1, and the discharge capacity, initial efficiency and capacity retention rate of the battery are improved. This seems to be because by appropriately forming the Mg-Si-ON film on the surface of the silicon-based particles of the present invention, the expansion of the material is effectively controlled and the conductivity of the carbon layer is increased. On the other hand, it can be confirmed that in Comparative Examples 1 to 4, the total content of N and H elements is less than 250 ppm or more than 3000 ppm, or the weight ratio of H element to N element in the active material is greater than 1, and in the negative electrode active materials of the comparative examples, the Mg-Si-ON film is not well formed on the surface of the silicon-based particles, or the hardness and elasticity of the formed Mg-Si-ON film are low, making it difficult to control expansion, thereby deteriorating the discharge capacity, initial efficiency and life characteristics of the battery.

Claims

1. A negative electrode active material, comprising: silicon-based particles containing SiOx (0 < x < 2) and a Mg compound; and a carbon layer provided on at least a part of the silicon-based particles, wherein the negative electrode active material contains N element and H element, wherein based on 100 parts by weight of the negative electrode active material, the total content of N element and H element is 250 ppm or more and less than 3000 ppm, and wherein the weight ratio of H element to N element is 1 or less.

2. The negative electrode active material according to claim 1, wherein based on 100 parts by weight of the negative electrode active material, the content of N element is 125 ppm or more and less than 3000 ppm.

3. The negative electrode active material according to claim 1, wherein based on 100 parts by weight of the negative electrode active material, the content of H element is 1 ppm or more and less than 1500 ppm.

4. The negative electrode active material according to claim 1, wherein the weight ratio of H element to N element is 0.1 or more and 1 or less.

5. The negative electrode active material according to claim 1, wherein at least a part of the N element exists in the form of Si-N bonds.

6. The negative electrode active material according to claim 1, wherein at least a part of the N element exists in the carbon layer.

7. The negative electrode active material according to claim 1, wherein the Mg compound contains Mg silicate.

8. The negative electrode active material according to claim 1, wherein based on 100 parts by weight in total of the negative electrode active material, the content of Mg element is 0.1 part by weight or more and 40 parts by weight or less.

9. The negative electrode active material according to claim 1, wherein based on 100 parts by weight in total of the negative electrode active material, the content of the carbon layer is 0.1 part by weight or more and 50 parts by weight or less.

10. A method for manufacturing the negative electrode active material according to any one of claims 1 to 9, the method comprising: vaporizing Si powder, SiO2 powder and Mg to obtain a mixed gas, and then cooling the obtained mixed gas to form silicon-based particles; and mixing the silicon-based particles with a carbon-based material to provide a carbon layer on at least a part of the surface of the silicon-based particles.

11. The method according to claim 10, further comprising heat-treating the silicon-based particles in a nitrogen atmosphere after forming the silicon-based particles.

12. The method according to claim 10, wherein when mixing the silicon-based particles with a carbon-based material to provide a carbon layer on at least a part of the surface of the silicon-based particles, NH3 gas is further included based on the carbon-based material.

13. A negative electrode, comprising the negative electrode active material according to any one of claims 1 to 9.

14. A secondary battery, comprising the negative electrode according to claim 13.

Citation Information

Patent Citations

  • Anode active material for lithium secondary battery, Anode comprising the same and Lithium secondary battery comprising the same

    KR1020190090730A

  • Bracket for mounting head lantern

    KR1020220150562A

  • Vacuum generator apparatus

    KR1020230154765A